2017
DOI: 10.1111/cen.13372
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity in relation to fat distribution and plasma adipocytokines among abusers of anabolic androgenic steroids

Abstract: Both current and former AAS abusers displayed lower insulin sensitivity which could be mediated by higher VAT and total body fat %, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 35 publications
1
41
0
6
Order By: Relevance
“…The study design and data on the primary hypotheses have been published previously. 6,10,[14][15][16] In brief, men (age: 18-50 years) involved in recreational strength training were enrolled in one of the following three groups: (1) current AAS abusers (n ¼ 37), (2) former AAS abusers who had discontinued AAS abuse ! 3 months before enrolling in the study (n ¼ 33), and (3) age-matched healthy control participants who denied ever having used AASs (n ¼ 30).…”
Section: Participants and Designmentioning
confidence: 99%
“…The study design and data on the primary hypotheses have been published previously. 6,10,[14][15][16] In brief, men (age: 18-50 years) involved in recreational strength training were enrolled in one of the following three groups: (1) current AAS abusers (n ¼ 37), (2) former AAS abusers who had discontinued AAS abuse ! 3 months before enrolling in the study (n ¼ 33), and (3) age-matched healthy control participants who denied ever having used AASs (n ¼ 30).…”
Section: Participants and Designmentioning
confidence: 99%
“…The association between AAS abuse and lipids has also been thoroughly studied and it has been persistently reported that AAS abuse is associated with slightly elevated levels of LDL cholesterol and decreased levels of HDL cholesterol. [43][44][45]60,61 In particular, intake of compounds that do not undergo aromatization into estrogen (e.g., stanozolol) seems to be associated with a marked decrease in HDL levels. 43 Although low-grade inflammation has been widely studied in the context of CVD, there is only limited information regarding inflammatory biomarkers and AAS abuse.…”
Section: Aas Abuse Thrombosis and Cardiovascular Risk Markersmentioning
confidence: 99%
“…61,62 Increased CRP was also demonstrated in 37 current AAS abusers compared with both former abusers and nonabusers. 60 Endothelial dysfunction is another core issue in relation to cardiovascular health. Two small studies used flow-mediated vasodilatation as a measure of endothelial function.…”
Section: Aas Abuse Thrombosis and Cardiovascular Risk Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Requirements were as follows: male, expressed intention of OX use, six months in AAS washout or never used AAS, and self-report of no drug treatment or history of cardiovascular, respiratory, hepatic, renal, musculoskeletal, or metabolic disorders [70,71]. This study included individuals who participated in a resistance-training program in the six months before the beginning of the evaluations.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%